2014
DOI: 10.1590/s2317-64312014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das ações da Fonoaudiologia no NASF da cidade do Recife

Abstract: Objetivo : Avaliar as ações da Fonoaudiologia nos Núcleos de Apoio à Saúde da Família da cidade do Recife (PE). Métodos : Foi realizado um estudo de avaliação com abordagem normativa, considerando os aspectos relacionados à estrutura e processo. Para a avaliação, foi elaborado o modelo lógico da atuação fonoaudiológica no Núcleo de Apoio, a partir da análise dos documentos oficiais que regulamentam a atuação nos Núcleos de Apoio à Saúde da Família. Em seguida, foi construída uma matriz de avaliação e elaborado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 14 publications
0
14
0
14
Order By: Relevance
“…Historically, this professional has been practiced strictly from a clinical point of view, with great value placed on specialist professional and the level of priority intervention at the secondary level of care (17) . However, with the creation of SUS and, latterly, with the 2008 emergence of Family Support Health Centres (Núcleos de Apoio à Saúde da Família: NASF), in which it is expected that SLH professionals will play an important role in the organization of the health system and the transformation of health service practices (18,19,20) within SUS, Primary Care has become an important sphere of operation for these professionals (17) . In the Northeast, this change is very well represented in João Pessoa, where we identified an evolution of the operations of SLH professionals in Primary Care between the periods prior to (2007) and following (2014) the establishment of the NASF.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, this professional has been practiced strictly from a clinical point of view, with great value placed on specialist professional and the level of priority intervention at the secondary level of care (17) . However, with the creation of SUS and, latterly, with the 2008 emergence of Family Support Health Centres (Núcleos de Apoio à Saúde da Família: NASF), in which it is expected that SLH professionals will play an important role in the organization of the health system and the transformation of health service practices (18,19,20) within SUS, Primary Care has become an important sphere of operation for these professionals (17) . In the Northeast, this change is very well represented in João Pessoa, where we identified an evolution of the operations of SLH professionals in Primary Care between the periods prior to (2007) and following (2014) the establishment of the NASF.…”
Section: Discussionmentioning
confidence: 99%
“…Among speech therapists from the city of Recife, it was found that the matrix support actions of NASF held in combination with the basic team overlapped clinical care rehabilitation 30 , which demonstrates organization of the staff in meeting the demand for shared consultation, which as recommended, should only take place in specific cases 13 .…”
Section: Discussionmentioning
confidence: 99%
“…It is understood that bringing speech-language therapists closer to these diverse realities assumes that their initial and ongoing training must consider the guidelines contained in public health and education policies while providing support for the systematization of speech-language actions that consider the social determinants involved in professional activity (6,7,10,11) . Regarding the academic background of the respondents and their institution of origin, it was found that in 2000 and 2011, the majority of respondents had completed an undergraduate degree in speech-language pathology within the Board's jurisdiction.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of the number of respondents employed in public institutions, as observed in the present study, follows the expansion of speech-language therapists working in the national healthcare system (4,7) , observed since 1990 due to: the creation of the Brazilian Society of Speech Committee of Public Health (12) ; changes to the national curriculum guidelines for undergraduate courses in speech-language pathology, which now prioritize country's healthcare system (13) ; teamwork and attention to comprehensive health and the inclusion of speech-language therapy in services related to the Family Health Strategy (6) . And finally, regarding changes related to the workplace, it is noteworthy that the increase of respondents' activity in regular schools and a reduction of activity in special schools are linked to Brazilian educational policies that state the education of students with special educational needs (PNEEs) must occur in the regular school system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation